Assessing Community Resilience against Climatic Disasters: A Case Study on Local Adaptation Strategies in the Barguna District - Md Mahir, Daiyan A; Syed Nazmus, Sakib A; ABM Kamal, Pasha A (INTI International University, 2025)
Natural disasters driven by climate change significantly impact the socio-ecological system, particularly in vulnerable regions like the Barguna District of Bangladesh. This study uses quantitative and qualitative methods to examine community resilience and local adaptation strategies against climate-induced disasters. Data were collected from 300 households, complemented by focus group discussions and key informant interviews. Geographic vulnerabilities, insufficient disaster education, and limited stakeholder representation exacerbate the challenges that Barguna communities face. The study reveals that 52.5% of respondents hold a negative outlook on their community’s future resilience to climate-induced disasters, with only 10.8% expressing a very positive perception and 4.9% being extremely optimistic about adaptation and recovery. These findings underscore critical gaps in policy implementation, resource allocation, and community engagement that hinder effective resilience-building. Analysis reveals that local coping mechanisms, while effective to some extent, require substantial enhancement to address the frequency and severity of disasters. Traditional methods such as crop diversification, soil management, and early warning systems are underutilized due to inadequate infrastructure and awareness. The study proposes an enhanced disaster management framework that integrates local knowledge with government policies, addressing the 40.67% lacking understanding of the Disaster Management Framework, the 45% advocating for community representation, and the 77% emphasizing the urgent need for targeted strategies to manage recurring cyclone threats in Barguna. This framework aims to strengthen community resilience, mitigate disaster impacts, and support sustainable development in Barguna. By bridging the gap between policy and practice, the research underscores the need for inclusive and context-specific disaster management strategies. The findings provide actionable recommendations to improve preparedness and reduce the socioeconomic and environmental repercussions of climate-induced disasters.